Synthesis of hydroxyapatite /Zeolite/Perlit hybrid coatings on human tooth by hydrothermal method and their in vitro behaviour - Tunc, Buesra; Muratoglu, Mehtap (Sage Publications Ltd, 2025)
Hydroxyapatite (HA) is prevalently employed as a biomaterial, courtesy of its bone-like resemblance. For the purpose of counterbalancing the frail mechanical attributes of unadulterated HA, the creation of bioceramic composite materials has been instigated. The goal of this investigation revolves around the endeavor to encapsulate human teeth by utilizing a HA-based dental composite powder, procured from perlite in conjunction with zeolite obtained via hydrothermal synthesis methodologies. Human teeth were gathered from dental practitioners, underwent a calcination process at an exponentially high temperature of 850 degrees C for three hours and subsequently transformed into a powdered state. Calcium nitrate (CaNO3) was indispensable as the calcium supplier, while phosphorus pentoxide (P2O5) was pivotal as the source of phosphorus. Different proportions (10%-50%) of perlite-converted zeolite were incorporated into the artificially synthesized Hydroxyapatite (HA). The prepared specimens were later subjected to a series of tests, including Scanning Electron Microscope (SEM), Energy Dispersive X-ray Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), investigation of surface roughness, and in vitro analyses. For in vitro test, samples were submerged in Ringer's solution and kept for periods of 1, 10, and 25 days. It became evident that an escalation in reinforcement quantity triggered a concurrent rise in parameters such as porosity and surface roughness value. It was also noted that a HA layer had established itself on the surface of the specimens according to the Ca/P proportion. With an increase in time spent submerged in the solution, a corresponding increase was observed in apatite formation.
Keywords: Biomaterials; hydroxyapatite; expanded perlite; zeolite; hydrothermal synthesis; hybrid-coating